EMI IN INDONESIAN HIGHER EDUCATION: STAKEHOLDERS' PERSPECTIVES - Simbolon, Nurmala (TEFLIN Journal, 2018)
Many universities in Indonesia are striving towards becoming internationally renowned universities. Partly, they do so by making English as Medium of Instruction (EMI). The university where the study was conducted commenced EMI through its voluntary EMI programs, which lasted for four years. The discontinuation of the EMI programs was the trigger of this study. This article seeks to understand the stakeholders' perspectives of EMI. Data were gathered from two focus group interviews involving six content-based lecturers and three policy makers in one state university which utilises EMI approach in their course delivery, and then analysed using thematic and content analysis methods. The findings demonstrate that while the stakeholders agree that mastery of English is important for their university graduates, there was a gap between policy makers' perspectives and the articulation of the institutional policy concerning the significance of English proficiency in the department's curriculum. Yet, the stakeholders admit that there is possibility that EMI can be implemented in several relevant departments in the university. The interviews also reveal that stakeholders consider content-based language teaching (CBLT), practised by language specialists, as the most suitable approach should EMI be implemented throughout their university. Finally, this article concludes with further EMI implications for university planning of its English language teaching.